Place marketing as an approach to planning place growth strategies - The case of Sydney Darling Harbour - Van, Hoang Thanh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2012)
Abstract. In the past three decades many cities and regions around the world have applied a marketing approach to place planning [Vp1]   in an effort to attract development resources, now called “place marketing”. This paper offers a critical review of the evolution of place marketing, discusses reasons for the evolution and then investigates place marketing practices through the case of Sydney Darling Harbour. Although [Vp2]   used in much earlier times, place marketing was mainly promotional, intuitive and random then. A more integrated and strategic implementation of place marketing has been evident in recent decades. Place marketing is considered to be both a consequence of, as well as a necessity for, increased competition between places for development resources. Darling Harbour is the starting point of a long-term and large-scale program of marketing the city of Sydney to its target markets - [Vp3]  transnational corporations (TNCs) and tourists. Although the way in which it has been implemented is debatable,DarlingHarbour is one of the most favoured attributes of the place product offered bySydney to the target markets. Keywords: Place marketing, city planning, place competition.   [Vp1] Please don’t remove. It is the key word.   [Vp2] Although should be replaced with another word?   [Vp3] What is this?